Regional horizontal ecological compensation and ecosystem service value based on water resources pattern and insurance gain - Jiao, Meng-Meng; He, Li; Wang, Yu-Xuan (Ying yong sheng tai xue bao, 2023)
Ecological compensation plays an important role in maintaining ecosystem services and promoting regional green development. We built a regional horizontal ecological compensation model based on water resources pattern and insurance gain, and which was used to solve the problems of single compensation method and low compensation efficiency. Taking the Beijing-Tianjin-Hebei region as an example, we analyzed water footprint and water ecological carrying capacity from 2000 to 2019. The compensation subject and object and water footprint compensation amount were determined according to the input cost of ecological protection and allocation factor. Then, the insurance pricing model was introduced to determine ecological insurance premium rate. We calculated insurance compensation, ecological compensation standard and different types of ecosystem service value. Results showed that the whole region was at a state of water ecological deficit, with the agricultural water footprint accounting for 94.5%. From the perspective of the compensation subject and object, Beijing and Tianjin, as the compensation subject, needed to pay 0.402 billion yuan and 0.396 billion yuan (the amount of compensation) to Hebei Province each year. Hebei Province obtained a total of 0.228 billion yuan of ecological insurance with an insurance premium rate of 1.4%, and should receive an average annual ecological compensation standard of 0.81 billion yuan from Beijing and Tianjin. Hydrological regulation was the core ecosystem service in the region, with an average value of 187.974 billion yuan. It was of strategic significance to introduce ecological insurance mechanism to construct horizontal ecological compensation mechanism, improve ecosystem service function, and enhance the value of ecosystem services in the study area.